Aktivitas Anti Agregasi Platelet dan Aktivitas Antitrombosis Ekstrak Etanol Daun Cinco (Cyclea barbata Miers.) - MARISSA ANGELINA; SRI HARTATI; INDAH DEWI; LIA MEILAWATI; IMACULATA IWO (Fakultas Farmasi Universitas Pancasila, 2012)
The research about anti aggregation platelet and antithrornbotic activity of ethanol extract of Cinco (Cyclea barbata Miers.) (Cb) leaves in mice has been conducted. The background of the research has been reported in vitro anti aggregation platelet and antithrombotic activity of Cb extract. The purpose of this research to know the effect of Cb extract in anti aggregation platelet, antithrombotic activity, prolonged the tail bleeding and coagulation time. The results of the present study indicate that the extract of Cb leaves significantly inhibit platelet aggregation in mice, prolonged tail bleeding time, coagulation time in mice, and thrombotic forming (acute). All of the above measurement have been analyzed significantly using One Way ANOVA programme. Cyclea barbata Miers. significantly prevented death due to thrombus protection whereas as in dose dependent manner. Cyclea barbata Miers. showed significant prolongation of the mice tail bleeding time compared to the control in low dose (150 mg/kg BW). Cyclea barbata Miers. significantly prolonged coagulation time compared to the control in dose dependent manner. The experiment on in vivo anti platelet aggregation showed that Cb (150 mg/kg BW and 300 mg/kg BW) could significantly inhibit aggregation which induced by ADP compared with control. The conclusion of this research is that the extract of Cb leaves has an anti aggregation platelet activity and antithrombotic activity in dose 150. mg/kg BW and 300 rug/kg BW.